Creating A Visually Rich, Active Learning Environment For Teaching Mechanics Of Materials - Wood, John; Bartolomei, Jason; Winebrener, Dave; Rhymer, Don; Self, Brian; Jensen, Daniel (Association for Engineering Education - Engineering Library Division Papers, 2002)
For the last 4 years we have been working to develop a suite of tools to enhance our Introduction to Mechanics course here at the US Air Force Academy (USAFA). The course is taught to over 1000 students per year and covers standard Mechanics of Materials content at a basic level. The course is required of all cadets at USAFA, so most of the students who take the course are not engineering majors. The objectives associated with this research program are four-fold: 1) to reach a student population that has a great variety of learning styles, 2) to increase overall motivation in the topic area, 3) to create a more active learning environment and 4) to present problems which are open ended and therefore have no single “right” solution. We endeavored to do this beginning from a sound pedagogical foundation and guided by a formalized, multifaceted assessment program. We are attempting to achieve the 4 objectives through the use of a multimedia tool in development called Vis-MoM (for Visual Mechanics of Materials). This interactive multimedia courseware is designed to span the space of learning styles by providing extensive visualization and interactive content as well as thorough, step-by-step example problems. We have previously shown that these particular features of our courseware correspond well to a full span of learning styles as illuminated by the Myers Briggs Type Indicator. Vis-MoM is designed to increase motivation through extensive use of real-world examples and an interactive, thought-provoking learning environment. Finally, we show the open-ended nature of the subject by inclusion of open-ended design problems for each topic. Three separate assessment techniques have been used to evaluate the effectiveness of the interactive multimedia courseware. Our assessment indicates the students’ perception of the learning tool is quite positive. However, there are some notable exceptions to this, which are detailed in the paper. In addition, our assessment shows that the visual modules did enhance understanding when compared to a traditional lecture format. This paper should provide others who are attempting to enhance mechanics courses with important information relevant to their development, implementation, and assessment processes. The Fundamentals of Mechanics course at the United States Air Force Academy (USAFA) was used as a testing ground for assessing the effectiveness of an interactive multimedia courseware tool called Vis-MoM (for Visual Mechanics of Materials). The course combines two basic topics in engineering mechanics (statics and strength of materials) at an introductory level and is mandatory for all students at USAFA regardless of major. Typically, the concepts of “Proceedings of the 2002 American Society for Engineering Education Annual Conference & Exposition Copyright © 2002, American Society for Engineering Education” Main Menu